The Myth of Informed Consent: An Analysis of the Doctrine of Informed Consent and Its (Mis)Application in HIV Experiments on Pregnant Women in Developing Countries - Dyckman, Jay (Columbia Journal of Gender and Law, 1999)
It has been just over fifty years since Nazi Germany taught the modem world the vicious consequences of utilizing politics and fascist ideology to shape and direct science, medicine, and health care. The horrific experiments and medical rationing conducted by the Nazi government fractured the idea that science and medicine aim to care for and protect the body, and exposed how politics necessarily drives decisions as to which “bodies” are worthy of protection. By constructing the Jew’s body as inherently inferior to the model Aryan physique, German doctors and scientists were able to create a justification for withheld care, coerced medical experimentation, and the final solution of annihilation. The legacy of these atrocities was a post-war declaration of the intrinsic uniqueness of each individual and the sacredness of each body. Called the Nuremberg Code, this document provides guidance to those in the medical field by structuring a means to achieve the goal of securing the bodily integrity of each human subject. The principle vehicle of the declaration is the doctrine of informed consent.